Loss of Axon Bifurcation in Mesencephalic Trigeminal Neurons Impairs the Maximal Biting Force in Npr2-Deficient Mice - Ter-Avetisyan, Gohar; Dumoulin, Alexandre; Herrel, Anthony; Schmidt, Hannes; Strump, Johanna; Afzal, Shoaib; Rathjen, Fritz G. (Frontiers in Cellular Neuroscience, 2018)
Bifurcation of axons from dorsal root ganglion (DRG) and cranial sensory ganglion (CSG) neurons is mediated by a cGMP-dependent signaling pathway composed of the ligand C-type natriuretic peptide (CNP), the receptor guanylyl cyclase Npr2 and the cGMP-dependent protein kinase I (cGKI). Here, we demonstrate that mesencephalic trigeminal neurons (MTN) which are the only somatosensory neurons whose cell bodies are located within the CNS co-express Npr2 and cGKI. Afferents of MTNs form Y-shaped branches in rhombomere 2 where the ligand CNP is expressed. Analyzing mouse mutants deficient for CNP or Npr2 we found that in the absence of CNP-induced cGMP signaling MTN afferents no longer bifurcate and instead extend either into the trigeminal root or caudally in the hindbrain. Since MTNs provide sensory information from jaw closing muscles and periodontal ligaments we measured the bite force of conditional mouse mutants of Npr2 (Npr2flox/flox;Engr1Cre) that lack bifurcation of MTN whereas the bifurcation of trigeminal afferents is normal. Our study revealed that the maximal biting force of both sexes is reduced in Npr2flox/flox;Engr1Cre mice as compared to their Npr2flox/flox littermate controls. In conclusion sensory feedback mechanisms from jaw closing muscles or periodontal ligaments might be impaired in the absence of MTN axon bifurcation.